2011
DOI: 10.3109/09638288.2011.635748
|View full text |Cite
|
Sign up to set email alerts
|

Feasibility, criterion validity and retest reliability of exercise testing using the Astrand-rhyming test protocol with an adaptive ergometer in stroke patients

Abstract: The Astrand-Rhyming test protocol and MOTOmed Viva2 adaptive ergometer were feasible in healthy participants. The protocol was not feasible for V·O(2max) estimation for the majority of stroke patients based on heart rate response. The adapted steady state VO2 measures used however were feasible and had strong relationship to actual VO2 consumption. Criterion validity and retest reliability of test data were excellent.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(13 citation statements)
references
References 38 publications
1
12
0
Order By: Relevance
“…Given present observations and its safety profile based on other studies in high-risk patients tested without complications (Lennon et al, 2012;Speelman et al, 2012;Thorsen et al, 2009), there appears to be no reason why physician attendance is required. In order to guarantee maximal safety, we recommend that the Astrand-Rhyming test is supervised by an experienced clinician (e.g., a mental health physical therapist) and should preferably be conducted in a setting which has medical cardiopulmonary resuscitation training expertise within a near proximity and on the same site location.…”
Section: Feasibilitysupporting
confidence: 53%
“…Given present observations and its safety profile based on other studies in high-risk patients tested without complications (Lennon et al, 2012;Speelman et al, 2012;Thorsen et al, 2009), there appears to be no reason why physician attendance is required. In order to guarantee maximal safety, we recommend that the Astrand-Rhyming test is supervised by an experienced clinician (e.g., a mental health physical therapist) and should preferably be conducted in a setting which has medical cardiopulmonary resuscitation training expertise within a near proximity and on the same site location.…”
Section: Feasibilitysupporting
confidence: 53%
“…The hip muscle group testing order was randomized at test session 1 (unrestricted randomization, computer random number generator), and the same order was maintained at session 2. The feasibility of the hip muscle RFD‐SF testing protocol was evaluated as testing compliance and the lack of adverse events . The construct validity of hip muscle RFD‐SF was evaluated as the presence of a linear relationship between torque and respective rate of torque development (RTD) for a series of fast isometric contractions performed over a wide range of intensities …”
Section: Methodsmentioning
confidence: 99%
“…The feasibility of the hip muscle RFD-SF testing protocol was evaluated as testing compliance and the lack of adverse events. 21 The construct validity of hip muscle RFD-SF was evaluated as the presence of a linear relationship between torque and respective rate of torque development (RTD) for a series of fast isometric contractions performed over a wide range of intensities. 13 All assessments were conducted under isometric conditions and consisted of MVC followed by fast contractions, from which torque was recorded by means of an isokinetic dynamometer (Biodex System 4; Biodex Medical Systems, Shirley, New York).…”
Section: Studymentioning
confidence: 99%
“…102 Studies using cycle ergometry after stroke have been unable to demonstrate accurate predictive equations of peak V . o 2 based on exercise test performance, 105,106 but a recent study that used total-body recumbent steppers found strong associations between actual and predicted peak V . o 2 .…”
Section: Preexercise Evaluationmentioning
confidence: 99%